The Model of Trauma Healing Policy for the Tsunami Disaster Mitigation in Padang, Indonesia - Asman, Aulia; Asman, Auzia; Alfina, Rina (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Padang City is one of the cities threatened by tsunami hazard in Indonesia. There have been many government efforts to reduce casualties and physical damage to development. But there has not been a focus mitigation step discussing the trauma healing. This research aims to develop a model of trauma healing policy for the mitigation of tsunami disaster in Padang. This research is qualitative research using the Analytical Hierarchy Process (AHP) as data analysis. The results of the study using three criteria i.e resources, education, and social values, religion and culture of society. These three criteria, in a succession of 4 policy priorities, i.e a) the enhancement of the resource psychiatrist/counsellor/therapyhis; b) Involvement of family and school citizens in the trauma healing Program; c) The increase of social, religious and cultural values in the process of trauma healing; and d) the implementation of non-farmalogi therapy programs that are targeted to disaster victims tailored to the needs. The priority of these policies can be achieved by implementing various program activities taking into account the implementation time and budget cost.